Inverse associations between dietary flavonoid and subclass intakes and frailty in U.S. adults - Cai, Shuangming; Huang, Shan; Xiao, Huanshun; Luo, Yiping (Frontiers in Nutrition, 2025)
ObjectivesDietary flavonoids, known for their antioxidant and anti-inflammatory properties, may play a role in frailty prevention, but comprehensive population-based studies are lacking. This study aimed to examine the associations between dietary flavonoid intakes and the prevalence of frailty in a nationally representative sample of U.S. adults, and to identify the predominant flavonoid subclasses contributing to these associations.MethodsCross-sectional data from 12,152 adults aged ≥20 years participating in the National Health and Nutrition Examination Survey (NHANES) 2007–2010 and 2017–2018 were analyzed. Dietary flavonoid intake was assessed using two 24-h dietary recalls. Frailty was defined using a 49-item frailty index. Weighted multivariate logistic regression models and restricted cubic spline analyses were employed to investigate the relationships between flavonoid intakes and frailty prevalence. Weighted quantile sum (WQS) regression and quantile g-computation (qgcomp) models were used to assess the mixed effects of flavonoid subclasses.ResultsHigher intakes of total flavonoids (OR:0.79, 95% CI:0.65–0.95), anthocyanidins (OR:0.71, 95% CI:0.58–0.88), flavanones (OR:0.74, 95% CI:0.59–0.92), flavones (OR:0.76, 95% CI:0.59–0.97), and flavonols (OR:0.67, 95% CI:0.56–0.81) were significantly associated with lower prevalence of frailty after adjusting for confounders. Non-linear inverse associations were observed for total flavonoids and flavonols. The WQS model revealed that the mixture of flavonoid subclasses was inversely associated with frailty odds (OR: 0.58, 95% CI: 0.48–0.71, p < 0.001), with flavones, flavonols, and anthocyanidins as the top contributors. The qgcomp model confirmed these findings but highlighted potential opposing effects among subclasses.ConclusionThis comprehensive analysis provides evidence that higher dietary flavonoid intakes, particularly flavones, flavonols, and anthocyanidins, are associated with lower prevalence of frailty in U.S. adults. These findings suggest that flavonoid-rich diets may be a promising strategy for frailty prevention, warranting further investigation through prospective cohort studies and randomized controlled trials.